Remarkable Similarity in Timing of Absorptive Fine-Root Production Across 11 Diverse Temperate Tree Species in a Common Garden - Withington, Jennifer M.; Goebel, Marc; Bułaj, Bartosz; Oleksyn, Jacek; Reich, Peter B.; Eissenstat, David M. (Frontiers in Plant Science, 2021)
Long-term minirhizotron observations of absorptive fine roots provide insights into seasonal patterns of belowground root production and carbon dynamics. Our objective was to compare root dynamics over time across11, mature temperate trees species: five evergreen and six deciduous. We analyzed the timing and growth on 1st-and 2nd-order roots in minirhizotron images down to a vertical depth of 35 cm, as well as monthly and total annual length production. Production patterns were related to total annual precipitation of the actual and previous year of root production over six years. The main or largest peak of annual fine root production occurred between June and September for almost all species and years. In most years, when peaks occurred, the timing of peak root production was synchronized across all species. A linear mixed model revealed significant differences in monthly fine root length production across species in certain years (species x year, P < 0.0001), which was strongly influenced by three tree species. Total annual root production was much higher in 2000-2002, when there was above-average rainfall in the previous year, compared with production in 2005-2007, which followed years of lower-than-average rainfall (2003-2006). Compared to the wetter period all species experienced a decline of at least 75% in annual production in the drier years. Total annual root length production was more strongly associated with previous year’s (P< 0.001) compared with the actual year’s precipitation (P= 0.003). Remarkably similar timing of monthly absorptive fine root growth can occur across multiple species of diverse phylogeny and leaf habit in a given year, suggesting a strong influence of extrinsic factors on absorptive fine root growth. The influence of previous year precipitation on annual absorptive fine root growth underscores the importance of legacy effects in biological responses and suggests that a growth response of temperate trees to extreme precipitation or drought events can be exacerbated across years.